UMP introduces Bachelor’s Degree in Applied Science (Data Analytics) - UMP, PNC (2019)
In response to the increasing demand for data scientists and analysts, the Faculty of Industrial Sciences & Technology (FIST) at Universiti Malaysia Pahang (UMP) recently announced the inauguration of a new degree programme called Bachelor of Applied Science (Honours) in Data Analytics.